Therapies used for the management of myofascial temporomandibular disorders: bibliometric analysis - Jessica Fernanda Lima Batista; Laércio Guedes de Lima; Sérgio Soares da Silva; Marcela Carla Nascimento; Miguel Meira e Cruz; Mônica Vilela Heimer (BrJP, 2024)
BACKGROUND AND OBJECTIVES: Temporomandibular disorder (TMD) is the term used to describe a set of painful and functional conditions that can affect the temporomandibular joint (TMJ), the masticatory muscles and/or their associated structures. For myofascial TMD, conservative therapies, including drugs, physical therapy, occlusal splint and pain self-management show the best benefits to the patient. The objective of this study was to carry out, through a bibliometric analysis, a review of the existing knowledge regarding the treatments used in myofascial TMD. CONTENTS: The search was conducted in the Web of Science (WOS) and SCOPUS databases in July and updated in December 2023, through the MeSh descriptors “Temporomandibular Joint Dysfunction Syndrome” and “Therapeutics”. Moreover, bibliometric mapping was performed using the VOSviewer software. For the analysis, data on the terms of the title and abstract, type of document, number of citations, name of journals, most cited article and year of publication were included. Besides these, the country of the corresponding author, type of treatment, type of study and the results were included in the analysis. Of the 760 articles identified, 63 were selected to compose this review. Of these, most were original articles, clinical trials and were published in 2012. The most frequent treatments were: occlusal splint, laser, manual therapy, botulinum toxin and dry needling. Of the 15 countries analyzed, Brazil was the country with the highest number of publications. CONCLUSION: There was an increase in articles published on the topic, with Brazil being the country with the highest number of publications. Finally, the most used treatments were occlusal splint and laser.